Description of two new species of Sindosium Johnson, 2007 from Australia (Coleoptera, Ptiliidae) - Nankervis, Jason F. Maté (Zootaxa, 2020)
As part of an ongoing inventory of the Australian fauna of Ptiliidae (Coleoptera, Staphylinoidea), several specimens were found in different berlesate samples from across the east coast of Queensland that did not conform to any of the genera currently known from Australia. The material proved to be two new species belonging to the genus Sindosium Johnson, 2007, Sindosium queenslandicum sp. n. and Sindosium lamingtoni sp. n. The species are described and compared to the other known species, a key to all known species is provided, and their distribution and biology are discussed.